PANDANGAN ETIKA KRISTEN TERHADAP IDENTITAS HOMOSEKSUAL - Christopher Alexander; Ferry Simanjuntak (Bethel Press, 2021)
The issue of homosexuality continues to be debated everywhere, both in psychology, biology and in theology. Arguments are exchanged to maintain the gay and opposing views of each other. The issue of homosexual identity is even more. The gay gene is the ultimate weapon launched by pro homosexuals to provide a protective wall for homosexuals. The self-justification of homosexuality also helps to be supported by using the bible as its proponency. On this occasion, the writer raised the topic